2011
DOI: 10.1038/nrneurol.2010.181
|View full text |Cite
|
Sign up to set email alerts
|

Dolichoectasia—an evolving arterial disease

Abstract: Dolichoectasia is an arterial disease that causes dilatation and/or tortuosity of the affected vessel. The prevalence of dolichoectasia increases with age, and this disease is also associated with other traditional cardiovascular risk factors. Multiple pathophysiological processes might lead to the development of dolichoectatic vessels, and activation of metalloproteinases and irregular turbulent blood flow seem to cause irreversible disruption of the internal elastic lamina. Intracranial dolichoectasia common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
164
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(181 citation statements)
references
References 88 publications
5
164
0
6
Order By: Relevance
“…In addition, we did not found that BAL, BL or TI of the BA were the risk factors of posterior circulation ischemic stroke, suggesting that dilation of BA was associated with perfusion of posterior circulation but tortuosity and elongation were not associated with the perfusion in territories of posterior circulation. A recent review on dolichoectasia demonstrated that dolichoectatic vessels that had large diameters seem to be associated with the greatest risk of stroke, while novel elongation and tortuosity were associated with compressive cranial neuropathies,1 this may support our findings. Though some VBD patients were involved with vertebral artery and some patients were determined to be ischemic stroke located in the areas fed by vertebral artery, we did not find that dilation or tortuosity of vertebral artery was the risk of posterior circulation ischemic stroke.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, we did not found that BAL, BL or TI of the BA were the risk factors of posterior circulation ischemic stroke, suggesting that dilation of BA was associated with perfusion of posterior circulation but tortuosity and elongation were not associated with the perfusion in territories of posterior circulation. A recent review on dolichoectasia demonstrated that dolichoectatic vessels that had large diameters seem to be associated with the greatest risk of stroke, while novel elongation and tortuosity were associated with compressive cranial neuropathies,1 this may support our findings. Though some VBD patients were involved with vertebral artery and some patients were determined to be ischemic stroke located in the areas fed by vertebral artery, we did not find that dilation or tortuosity of vertebral artery was the risk of posterior circulation ischemic stroke.…”
Section: Discussionsupporting
confidence: 88%
“…Increased BA diameter is the risk factor of future stroke 1, 18. In the GENIC study, Pico et al19 even found that BA diameter was associated with an increased 5‐year stroke mortality rate in patients with stroke and a diameter >4.3 mm might be a marker for a high risk of fatal stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing lesions are generally associated with high rates of rupture, ischemic stroke, and compressive symptoms, and imaging follow-up could potentially be used to identify at-risk lesions so that therapies can be put in place to mitigate the poor natural history of these lesions. 1,5,8,22,23 It is important to note, however, that there are no specific medical, surgical, or endovascular therapies specific to the treatment of VBDAs. In terms of stroke prevention, some studies have suggested that anticoagulation and antiplatelet therapy are not effective in preventing stroke in VBDAs and may be associated with higher hemorrhage rates, 24,25 whereas other studies have suggested that anticoagulation may be protective against mortality.…”
Section: Discussionmentioning
confidence: 99%
“…9 This study retrospectively reviewed the clinical and imaging data of 9 patients with VBD who were treated with coil-assisted stent reconstruction in the vascular lumen, in an attempt to explore the feasibility and long-term effectiveness of this technique in preventing ischemic events in stented vessels.…”
mentioning
confidence: 99%